Pola Pembelajaran yang Dilakukan oleh Dosen dalam Mengembangkan Kesadaran Beretika pada Mahasiswa Akuntansi: (Studi Kasus pada Jurusan Akuntansi STIE Mahardhika Surabaya) - Anggi Oktita Wati; Amin Sadiqin; Miya Dewi Suprihandari (JOURNAL OF ECONOMICS, BUSINESS, MANAGEMENT, ACCOUNTING AND SOCIAL SCIENCES, 2024)
This study aims to examine the learning patterns applied by lecturers in developing ethical awareness in accounting students at STIE Mahardhika Surabaya. Ethical awareness is one of the important aspects in accounting education, considering the role of accountants in maintaining integrity and transparency in financial reporting. The research method used is a case study with a qualitative approach, which involves observation, in-depth interviews, and document analysis. The results showed that lecturers used various learning strategies, such as case discussions, simulations, and integration of ethical values into the curriculum, to strengthen students' understanding and ethical awareness. It was also found that varied and interactive learning patterns contributed significantly to the improvement of students' ethical awareness. This study concludes that the development of ethical awareness in accounting education can be more effective if supported by learning methods that are contextual and relevant to the ethical challenges faced in the real world.